Pyoderma gangrenosum in myelodysplasia and acute leukaemia. Issue 718 (August 1985) - Jacobs, P.; Palmer, S.; Gordon-Smith, E. C.
Abstract : Pyoderma gangrenosum is a rare occurrence in patients with haematological malignancy. This characteristic but nonspecific inflammatory process with skin destruction occurred in 4 patients with myelodysplasia, in one with acute leukaemic transformation of myelofibrosis, and in de novo acute myeloblastic leukaemia in another. Clinically, the cutaneous lesion in these patients differed from that associated with inflammatory bowel disease, arthritis, or the idiopathic type of pyoderma gangrenosum by having the vesiculo-bullous borders. Histopathological differences were also evident since more superficial layers of the skin were involved in the ulceration than typically encountered in patients with non-malignant systemic disease. Despite the less penetrating nature of this variant, treatment of the pyoderma gangrenosum is unsatisfactory and in the absence of effective therapy for the underlying disease, healing occurred only in the patient with acute leukaemia who achieved complete remission in response to chemotherapy.